Clues to the “How” of Homeopathy - Mearns, Marci (Homœopathic Links, 2012)
At the 2012 Annual Joint American Homeopathic Conference, Dr. Luc Montagnier outlined his teamʼs newest findings and their implications for the medicine of the future in a presentation on the “Transduction of DNA Sequences from Pathogenic Microorganisms through High Dilutions of Water”. The upcoming JAHC 2013 promises a similar level of presentations.
Keywords: Memory of water; Transduction of DNA sequences; Electromagnetic signals